Sexually Active Adolescent Women: Assessing Family and Peer Relationships Using Event History Calendars - Saftner, Melissa Ann (2011)
The purpose of this qualitative study is to explore family and peer relationships (including support and influence on risk behavior) among sexually active European American and African American adolescent girls in the context of risk behaviors documented on retrospective event history calendars (EHCs) and in interviews. The EHCs were completed by the adolescents prior to a clinic visit with a nurse practitioner at a school-based clinic in Southeast Michigan, and interviews were conducted after the visit. Constant comparative analysis of EHCs and interview data of 19 sexually active 15 to 19-year-old girls revealed that those with positive familial and peer support were less likely to report risk behaviors compared to those with poor family and peer relationships. School nurses and other providers working with adolescents to prevent risk behaviors could utilize the EHC to determine risks and develop education plans and interventions to reduce risk behaviors.